"أثر جودة الحياة الوظيفية على الأداء الوظيفي: دراسة ميدانية على العاملين في كلية التربية العجيلات ومعهد شؤون المياه والتربة (Comprehensive Journal of Science, 2026)
This study aimed to determine the level of Quality of Work Life (QWL) and the level of Job Performance (JP) among employees at the College of Education Al Ajaylat and the Institute of Water and Soil Affairs. It also sought to reveal the nature of the correlation between the two variables and investigate the existence of statistically significant differences in JP attributable to the variables of gender and years of experience. The study adopted the Descriptive-Analytical Methodology and was applied to a sample of (112) male and female employees, using a questionnaire as the main data collection tool.Key Findings:The employees' perception of Quality of Work Life (QWL) was high, with dimensions like justice and fairness being the strongest, while health and social care were the weakest.The level of Job Performance (JP) was also rated as high, showing excellence in adherence to quality standards, but relative weakness in proposing innovative solutions.A strong, positive, and statistically significant correlation was found between QWL and JP (correlation coefficient 0.780), confirming that investment in the work environment positively impacts performance.Statistically significant differences were found in JP based on the gender variable, in favor of males.Statistically significant differences were found in JP based on the years of experience variable, in favor of employees with 10 years or more of experience.Main Recommendations: The study recommended the necessity of enhancing social and health care programs, activating a culture of administrative innovation, and reviewing evaluation policies to ensure equal opportunities between genders.
Keywords: Core Variables Dimensions of Quality of Work Life Dimensions of Job Performance Context and Theories